2021
DOI: 10.7759/cureus.12614
|View full text |Cite
|
Sign up to set email alerts
|

A Missed Bilateral, Acute Anterior Exertional Compartment Syndrome of the Leg

Abstract: A 26-year-old male athlete presented to our hospital with bilateral leg pain after intense training. He had a history of transient numbness and pain with rigorous exercise but this time pain persisted and drop foot developed. Unfortunately, the diagnosis of acute exertional compartment syndrome was delayed due to late presentation of the patient in our department. He underwent three consecutive surgeries for decompression and debridement. At 13 months follow-up, he is ambulatory with bilateral ankle-foot ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This is a rare, but potentially devastating condition, described in several case reports. 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a rare, but potentially devastating condition, described in several case reports. 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ICP measurements are still performed as part of standard care to determine a possible indication for early surgical treatment and to estimate the risk of developing an acute on chronic compartment syndrome. 11 , 12 , 13 However, the invasive nature of ICP measurements is associated with a risk of (asymptomatic) hematoma formation and the possibility to penetrate nerves or arteries. 14 , 15 Therefore, the need to measure ICP prior to conservative treatment for service members suspected of ant-CECS should be evaluated.…”
mentioning
confidence: 99%
“…Assessment of chamber pressure is helpful in determining the diagnosis, especially in patients with unresponsive diseases. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of chamber pressure is helpful in determining the diagnosis, especially in patients with unresponsive diseases. [15] The exact pathophysiological mechanisms of acute exertional OCS remain unclear. [16][17][18][19] During exercise, it has been reported that muscle volume can increase by up to 20% and that hydrostatic pressure in tissues increases due to poor compliance of the muscle compartment.…”
Section: Discussionmentioning
confidence: 99%